Sensory Marketing Model Based on Consumer Nostalgic Preferences in the Retail Industry - Sadeghitabar, Vahid; Rostami, Mohammadreza; Hosseini, Seyyed Hossein; Sanei, Mehdi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The objective of this study is to design a sensory marketing model based on consumer nostalgic preferences in the retail industry. Methodology: To achieve this, a qualitative research method, specifically grounded theory (Strauss & Corbin), was employed. The research population consists of experts and faculty members in business and management (e.g., branding, marketing, and management), from whom interviews were conducted. To collect data, in-depth interviews were utilized. Findings: The findings of the research revealed five main dimensions: 1) Developing lasting shopping experiences (designing retail spaces based on nostalgic symbols, using retro products and packaging, creating interactive experiences based on nostalgic symbols, maintaining fairness and respect toward consumers in an old-fashioned manner, and connecting with customers through storytelling), 2) Utilizing nostalgic elements (using old and nostalgic images and videos, incorporating nostalgic styles, leveraging old experiences and events, combining old technologies with nostalgic feelings, and using nostalgic sounds and music), 3) Rebuilding brands and products based on nostalgic behaviors (producing digital content to evoke nostalgic feelings, designing and packaging products in a nostalgic manner, reconstructing advertising and marketing based on nostalgic feelings, collaborating with influencers based on nostalgic feelings, and committing to product quality and sustainability), 4) Creating a deep connection between the brand and customer memories (maintaining continuous relationships with customers based on past attachments, organizing participatory events based on past promotions, enhancing customer experience through nostalgic behavior reflections, providing differentiated after-sales services, and obtaining active feedback and interaction from customers based on nostalgic behaviors), and 5) Developing creative nostalgic approaches (offering special products based on nostalgic elements, organizing nostalgic-themed raffles, creating interactive and nostalgic campaigns on social media, developing competitive pricing based on consumers’ nostalgic preferences, and strengthening emotional connections with nostalgic symbols). Conclusion: In conclusion, this study highlights the significant role of nostalgic elements in shaping sensory marketing strategies in the retail industry. By identifying key dimensions such as the development of sustainable shopping experiences and brand revitalization based on nostalgic behaviors, the research underscores the importance of creating deep emotional connections with consumers.